Polio Eradication–Lessons from the Past and Future Perspective - Swati Jain; Basavaraj.P; Shilpi Singh; Ashish Singla; Hansa Kundu; Khushboo Singh (Journal of Clinical and Diagnostic Research, 2014)
Background: India has recently achieved the “Polio free status” by WHO with stringent efforts of the Health Ministry to control its spread. However, we should not forget the lessons learnt from the failure of National malaria eradication Programme and National Tuberculosis control Programme which creates a need to assess the probable barriers for the various National Health Programmes. The present article presents an overview of the Polio Eradication programme in India highlighting the lessons learnt from the past. Also, it evaluates the reality behind full participation of Pulse Polio Programme. Materials and Methods: The study results of a cross-sectional survey conducted with an aim to assess the probable reasons and barriers behind non compliance of Pulse Polio Programme among parents of children (1-5 yr of age) of Modinagar area have also been discussed. The survey instrument was a structured, 10 item, closed ended questionnaire. Statistical analysis used: Chi-square test was used to analyze the difference between proportions of individual responses for each question and multiple logistic regression was used to assess relation between socio demographic parameter and absence from Polio Ravivaar. Results: The study reveals a surprising 68% attendance of Pulse Polio programme which is far behind the desired goal. Most of the parents who did not attend polio ravivaar considered that there was no need for the repetition of Polio vaccine (76.9%) followed by their fear that the vaccine might get contaminated during transportation (74.5%). A significant positive association was found between older age group of the eligible children (4-5 yr, O.R.1.52), female gender, illiterate parents, distance of more than one km from residence to vaccination and lack of source of information (O.R. 1.47). Conclusion: Efforts should be done to investigate the probable reasons behind non compliance for various immunization programmes to analyse the current situation in detail and formulate appropriate programs for coming years so that the efforts so far don’t go in vain and we secure a healthy Polio free nation for our future generations.